2005
DOI: 10.17705/1cais.01610
|View full text |Cite
|
Sign up to set email alerts
|

Management of Virtual Project Teams: Guidelines for Team Leaders

Abstract: This article offers a set of guidelines to assist project leaders when managing virtual project teams. The guidelines were developed as a result of a panel at the celebration of the 30 th anniversary of the founding of the MIS department at the University of Arizona. These guidelines include recommendations for addressing challenges that occur over the virtual team project life cycle, including identifying appropriate team members, establishing conventions and norms, and creating shared awareness. We also give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 21 publications
(14 reference statements)
0
25
0
1
Order By: Relevance
“…When decision projects end, DMs should consider how the process might be improved (Beranek et al, 2005). Sharing these ideas will help people both inside and outside the group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When decision projects end, DMs should consider how the process might be improved (Beranek et al, 2005). Sharing these ideas will help people both inside and outside the group.…”
Section: Discussionmentioning
confidence: 99%
“…Remote DMs might be used to different norms. The greater the differences, the more important it is that team leaders continue to address norms (Beranek et al, 2005). F2F communication is generally better for this than CMC (Kiesler and Cummings, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[29]) and virtual teams (e.g. [2][6] [9]), as well as on stages in creating and sustaining trust in virtual teams which show certain similarities to the overall virtual team lifecycle (e.g. [7]).…”
Section: Leading Virtual Teams Across Their Lifecyclementioning
confidence: 99%
“…However, the creation of effective virtual teams represents certain challenges for the organization. These challenges include the creation of trust in a virtual environment [7], communication across time zones [14] with little or no face-to-face contact [7] and across different cultures with help of information technology, as well as the creation of team-spirit and motivation [2]. Previous research found that leadership is an important factor to virtual team effectiveness [14] [28].…”
Section: Introductionmentioning
confidence: 99%